PENGGUNAAN METODE MONTE CARLO DAN EXPECTED MONETARY VALUE DALAM PREDIKSI PENJUALAN PRODUK - putra, farhan maulana; Sriningsih, Riry (Journal of Mathematics UNP, 2024)
Trade is a sector that significantly contributes to national economic growth, but the lack of understanding of marketing strategies has led many traders to incur losses. The rapid development of information and communication technology requires increasingly modern human activities. Various complex problems can be modeled and simulated first before being implemented, resulting in optimal outcomes. One of the strategies for preparing stock is to avoid stock shortages and surpluses. The Monte Carlo method and Expected Monetary Value are two methods used for making predictions. The forecasted sales figures for the Legenda gepeng product for the years 2024-2025 are 739,914 packs, Legenda Premium 54,201 packs, and Legenda Pia 137,750 packs. The lowest MAPE for each product is 17.59%, 33.24%, and 25.17% respectively.